2018
DOI: 10.3389/fphar.2018.01199
|View full text |Cite
|
Sign up to set email alerts
|

To Protect and to Preserve: Novel Preservation Strategies for Extracellular Vesicles

Abstract: Extracellular vesicles (EVs)-based therapeutics are based on the premise that EVs shed by stem cells exert similar therapeutic effects and these have been proposed as an alternative to cell therapies. EV-mediated delivery is an effective and efficient system of cell-to-cell communication which can confer therapeutic benefits to their target cells. EVs have been shown to promote tissue repair and regeneration in various animal models such as, wound healing, cardiac ischemia, diabetes, lung fibrosis, kidney inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 217 publications
1
138
0
Order By: Relevance
“…It should be noted that different laboratories use diverse methods to isolate and purify MSC-EVs and, accordingly, it is critical to define and standardize highly effective method for MSC-EV yields [31]. Additionally, clinical applications of MSC-EVs require their long-term use and considerable thought must be given to the preservation of their immunosuppressive potential [21]. A large number of studies demonstrated that the most convenient mode of storage for MSC-EVs remains −80 • C [109].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that different laboratories use diverse methods to isolate and purify MSC-EVs and, accordingly, it is critical to define and standardize highly effective method for MSC-EV yields [31]. Additionally, clinical applications of MSC-EVs require their long-term use and considerable thought must be given to the preservation of their immunosuppressive potential [21]. A large number of studies demonstrated that the most convenient mode of storage for MSC-EVs remains −80 • C [109].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies demonstrated that the most convenient mode of storage for MSC-EVs remains −80 • C [109]. Nevertheless, due to the complex cold chain logistics, alternatives such as lyophilization and the incorporation of additives might be necessary to improve MSC-EV storage stability during transportation [21,109].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review summarized the recommended preservation and storage methods for EVs, 69 and some consensus is emerging towards using −80°C for EV transportation and storage. 70,71 However, temperatures of around −80°C, may alter the functional activities, while storage at 4°C causes EV damage and aggregation.…”
Section: Long-term Preservation and Storage Stability Of Evsmentioning
confidence: 99%
“…The addition of cryoprotectants (eg sugars, amino acid, etc. ), may help preserve EVs and their cargo 69 with good effects found in particular using trehalose. 65,74 Freeze-drying with a cryoprotectant does not seem to significantly affect EVs, and enzymes within the lyophilized EVs were found to exhibit activity comparable to that of EVs stored at −80°C.…”
Section: Long-term Preservation and Storage Stability Of Evsmentioning
confidence: 99%
See 1 more Smart Citation